Characterization and antioxidant activity ofseed oil avocado Persea americana Mill. - Rengifo, Pedro G. (2015)
Avocado seed is a part of the fruit discarded in industrial pulp oil extraction and would be a source of essential fatty acids and other phytoconstituents. This research aimed to characterize oil seed Persea americana Mill. Var. Hass and Fuerte and its antioxidant activity. To oil obtained by the Soxhlet method, was made the physicochemical characterization following the AOCS (American Society of Chemical Oil) standards, the fatty acid profile by gas chromatographic method and the antioxidant activity by the DPPH method. Physicochemical characterization reported mean values and standard deviation of 2,12±0,015; 1,40±0,047; 242,30±5,449; 70,62±2,82 and 0,919±0,024 to acidity index, peroxide, saponification, iodine and specific gravity, respectively; with significance p <0,05. Were identified two essential fatty acids: linoleic acid (48,77%) and linolenic acid (12,17%), omega-6 and omega-3, respectively. Finally, the antioxidant activity expressed in μmol TE/kg, tuvo valores de 9,676±0,260; 8,700±0,260 and 7,37±0,169 for total oil, saponifiable and unsaponifiable fraction, respectively. Characterized oil had a quality comparable to the extra virgin olive oil and its antioxidant activity would due to the presence of polyphenols and steroids.